A cross-sectional study assessing the effectiveness of hygiene related interventions and education delivered in an afterschool club in urban slums of Gurugram - Bhartiya, Shibal; Singh, Tarundeep (International Journal Of Community Medicine And Public Health, 2023)
Background: There is insufficient evidence about the effectiveness of hygiene related interventions and education delivered to out of school children, attending non-formal schools in urban slums. Methods: This cross sectional, interventional study was conducted from January 2022 to April 2022 in a non-formal school in an urban slum in Gurugram, Haryana. A validated questionnaire about hygiene related practices was used to record the behavioural practices of these children before and after education about hygienic practices. The children were also provided with soap, detergent, and four sets of clothes to enable them to follow the hygienic practices. The pre and post intervention status of various hygiene variables was compared. A p<0.01 was considered as statistically significant. Results: Of the 97 children included in this interventional study, 54 were boys. All of them were from the lower socioeconomic class, with 93% of the mothers and 98% of the fathers being illiterate. The percentage of unhygienic practices decreased significantly post intervention. All the p values for comparison between the pre and post intervention status of various hygiene variables were highly significant statistically (p=0.001). Maximum improvement was seen in case of brushing teeth, cutting nails, using footwear and bathing (2.86). Similarly, the total mean score for unhygienic practices (higher score indicating more unhygienic practices) for pre intervention was 30.62 which decreased to 10.54, indicating a total improvement of 20.08. Conclusions: Hygiene related interventions including continuing education, and provision of clothes and detergent, can improve hygienic practises in out of school children who attend non-formal schools in slums.